Frequency of Anxiety and Depression in Dissociative Trance (Possession) Disorder (Journal of Fatima Jinnah Medical University, 2021)
ABSTRACTBackground: The possession of a person by God or spirit is an age old one. The ICD-10 has recorded the presence of a possession and trance disorder before formal featuring it in 10th edition as category of dissociative (conversion) disorders. The current study sought to determines the frequency of anxiety and depression among the patients presented in tertiary care hospital with dissociative trance (possession) disorder, along with gender differences.Patients and Methods: This cross-sectional study was conducted at Department of Psychiatry, Sir Ganga Ram Hospital Lahore over the period of one year: December 2019 till December 2020. A sample of 350 patients, who met the ICD-10 criteria of dissociative trance (Possession) disorder, was recruited in the study through purposive sampling technique. Demographic information sheet and Urdu version of Hospital Anxiety and Depression (HAD) rating scale were used as assessment measures. The data was stored and analyzed in SPSS version 20. Descriptive analysis i.e., means, standard deviations, percentages and frequencies, and inferential statistics i.e., independent sample t-test, were performed in order to explore objectives.Results: The results indicate that 13.2 % of patients with dissociative trance disorder scored in normal range of depression, 20.7% fall in borderline depression while abnormal case of depression was found in 66.1% of patients. For anxiety, results demonstrates that 28.2% of patients fall in the category of normal anxiety, 3 31.5% in borderline anxiety and 40.3% fall in the case of abnormal anxiety. Differences for gender of patients in depression and anxiety scores were evaluated by independent sample t-test  and significant differences were found in depression and anxiety scores of male and female patients with dissociative trance disorder (p
Keywords: Dissociative trance disorder; Possession; Depression; Anxiety